The poverty wars : reconnecting research with reality - Saunders, Peter, 1948- (James Bennett Etitle., 2005)
Saunders argues that as a nation Australia can afford to eliminate financial poverty. The fact that we don't do so is a matter of choice, not affordability - as the experience of other countries demonstrates. In challenging this idea, this book focuses on how looking at poverty differently can help to make a world without poverty a practical reality.